2013
DOI: 10.4081/ejh.2013.e39
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of matrix proteins in the craniofacial cartilage in midterm human fetuses

Abstract: Immunohistochemical localization of collagen types I, II, and X, aggrecan, versican, dentin matrix protein (DMP)-1, martix extracellular phosphoprotein (MEPE) were performed for Meckel’s cartilage, cranial base cartilage, and mandibular condylar cartilage in human midterm fetuses; staining patterns within the condylar cartilage were compared to those within other cartilaginous structures. Mandibular condylar cartilage contained aggrecan; it also had more type I collagen and a thicker hypertrophic cell layer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 44 publications
(85 reference statements)
6
36
0
1
Order By: Relevance
“…Our findings from histological and histochemical studies of mice support this narrow definition (Shibata et al, ; ; ; Shibata and Yokohama‐Tamaki, ). Recently, we analyzed human midterm fetuses, focusing on the matrices of human mandibular condylar cartilage, including the perichondrium, and confirmed that this definition is also valid for human (Shibata et al, ). In addition, we demonstrated that tenascin‐ C is a marker of periosteum in human fetuses, and the perichondrium of condylar cartilage has characteristics of the periosteum (Shibata et al, ).…”
supporting
confidence: 62%
“…Our findings from histological and histochemical studies of mice support this narrow definition (Shibata et al, ; ; ; Shibata and Yokohama‐Tamaki, ). Recently, we analyzed human midterm fetuses, focusing on the matrices of human mandibular condylar cartilage, including the perichondrium, and confirmed that this definition is also valid for human (Shibata et al, ). In addition, we demonstrated that tenascin‐ C is a marker of periosteum in human fetuses, and the perichondrium of condylar cartilage has characteristics of the periosteum (Shibata et al, ).…”
supporting
confidence: 62%
“…Furthermore, we have examined expression patterns of collagen types I, II and X in human cranial base cartilage which undertook endochondral ossification at 16 weeks of gestation [12]. Since digit cartilage in the present study did not undertake endochondral ossification, collagen type X immunoreactivity was very weak, but expression patters of these collagen types were similar to those in cranial base cartilage at 16 weeks of gestation, indicating these collagen types have universal function in developing human long bones.…”
Section: Matrix Components In Digit Cartilage Compared With Condylar mentioning
confidence: 63%
“…We also demonstrated that chondrocytes in initially formed condylar cartilage is rapidly differentiated into hypertrophic chondrocytes, and simultaneously expresses many kinds of matrix components including collagen types I, II, X, aggrecan, versican, hyaluronan, bone sialoprotein and osteopontin [7][8][9][10][11]. In human, we demonstrated that the newly formed condylar cartilage is continuous with the ossifying mandible [8], and also demonstrated that immunohistochemical localization of matrix proteins in already formed condylar cartilage in midterm fetuses [12]. However, no immunohistochemical studies have been done in newly formed condylar cartilage in human.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations